Quantification of Alternative Splicing Variants of Human Telomerase Reverse Transcriptase and Correlations with Telomerase Activity in Lung Cancer - Liu, Yan; Wu, Bing-quan; Zhong, Hao-hao; Tian, Xin-xia; Fang, Wei-gang (PLOS ONE, 2012)
Telomerase plays important roles in the development and progression of malignant tumors, and its activity is primarily determined by transcriptional regulation of human telomerase reverse transcriptase (hTERT). Several mRNA alternative splicing variants (ASVs) for hTERT have been identified, but it remains unclear whether telomerase activity is directly associated with hTERT splicing transcripts. In this study, we developed novel real-time PCR protocols using molecular beacons and applied to lung carcinoma cell lines and cancerous tissues for quantification of telomerase activity and three essential hTERT deletion transcripts respectively. The results showed that lung carcinoma cell lines consistently demonstrated telomerase activity (14.22–31.43 TPG units per 100 cells) and various hTERT alternative splicing transcripts. For 165 lung cancer cases, telomerase activity showed significant correlation with tumor differentiation (poorly->moderately->well-differentiated, P<0.01) and with histotypes (combined small cell and squamous cell carcinoma>squamous cell carcinoma>adenosquamous carcinoma>adenocarcinoma, P<0.05). Although the overall hTERT transcripts were detected in all the samples, they were not associated with telomerase activity (r = 0.092, P = 0.24). Telomerase activity was significantly correlated with the transcriptional constituent ratio of α-deletion (r = -0.267, P = 0.026), β-deletion (r = -0.693, P = 0.0001) and γ-deletion (r = –0.614, P = 0.001). The positive rate and average constituent ratio of β-deletion transcripts (92.12%, 0.23) were higher than those of α-deletion (41.82%, 0.12) or γ-deletion (16.36%, 0.18) transcripts. The combined small-cell and squamous cell carcinomas expressed less deletion transcripts, especially β-deletion, than other histotypes, which might explain their higher telomerase activity. In conclusion, the molecular beacon-based real-time PCR protocols are rapid, sensitive and specific methods to quantify telomerase activity and hTERT ASVs. Telomerase activity may serve as a reliable and effective molecular marker to assist the evaluation of histological subtype and differentiation of lung carcinomas. Further studies on hTERT deletion splicing transcripts, rather than the overall hTERT transcripts, may improve our understanding of telomerase regulation.